2001
DOI: 10.4269/ajtmh.2001.65.442
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of lymphocytes, but not eosinophils, by Fas-mediated apoptosis in murine schistosomiasis.

Abstract: Abstract. Infection with the helminth parasite Schistosoma mansoni is associated with a pathogenic granulomatous response to parasite eggs. Multiple cell types constitute the granuloma with eosinophils achieving numerical dominance. We hypothesize that eosinophil dominance is achieved by selective apoptosis in lymphocytes. We report here that lymphocytes from both the spleens and granulomas of S. mansoni-infected mice undergo apoptosis. We also show that granuloma lymphocytes are more susceptible to Fas-FasL-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…This downregulation of Bcl-2 expression may contribute to viral persistence and progression of liver disease in chronic hepatitis C. It was also shown that signal transducer and activator of Bcl-2 was significantly stimulated in HCV-infected patients [37,38].…”
Section: Discussionmentioning
confidence: 93%
“…This downregulation of Bcl-2 expression may contribute to viral persistence and progression of liver disease in chronic hepatitis C. It was also shown that signal transducer and activator of Bcl-2 was significantly stimulated in HCV-infected patients [37,38].…”
Section: Discussionmentioning
confidence: 93%
“…Although the parasite-stimulated Th response peaks during the early stages of infection, it declines with the progression of infection to the chronic stages in a process referred to as immunomodulation (Maizels et al 2004). It was found that such immunomodulation is due to the Fasmediated apoptosis of lymphocytes, but not eosinophils, in murine schistosomiasis (Rumbley et al 2001). In humans, IL-10 was suggested to be an important cytokine in regulating the immune response and possibly controlling morbidity of human schistosomiasis mansoni, and that the production of interferon gamma (IFN-γ) might be associated with resistance to infection (reviewed in Corrêa-Oliveira et al 1998).…”
Section: Use Of Murine Hosts To Study Immunopathologymentioning
confidence: 97%
“…In schistosomiasis, T cell apoptosis in egg granulomas from schistosome-infected BL/6 mice was first described by Rumbley et al (49); these authors later postulated that the apoptosis was precipitated by SEA and was mediated by Fas, although an exceedingly high amount of Ag was required to achieve a relatively modest in vitro effect (29). Lundy and Boros (30) similarly reported Fas-mediated splenic CD4 ϩ T cell apoptosis precipitated by FasL-expressing CD5 ϩ B-1a cells, which, in turn, were induced by IL-10 and IL-4 produced by the same CD4 ϩ T cells stimulated with SEA; however, this mechanism of apoptosis could not be demonstrated in granuloma CD4 ϩ T cells.…”
Section: Figure 7 Ril-2 Treatment In Vivo Inhibits Granuloma Cd4mentioning
confidence: 99%
“…However, the failure of SEA to influence CD4 ϩ T cell apoptosis in vitro, together with the lower expression of the activation markers CD69 (40) and CD25 (41,42) in the granuloma and MLN cells ( Table I), suggested that the observed apoptosis in the BL/6 mice was not a manifestation of AICD. Nevertheless, we formally investigated the Fas/FasL pathway, particularly because it had been previously implicated in activation-induced CD4 ϩ T cell apoptosis in context with the schistosome infection (29,30). Analysis after a 36-h culture period, indeed, revealed a significantly higher proportion of Fas on granuloma CD4 ϩ T cells, and FasL on bulk granuloma cells from the CBA mice with low apoptosis (Fig.…”
Section: Fas and Fasl Are Not Involved In The Apoptosis Of Cd4mentioning
confidence: 99%